2021
DOI: 10.1109/tcds.2018.2889223
|View full text |Cite
|
Sign up to set email alerts
|

A Regression Method With Subnetwork Neurons for Vigilance Estimation Using EOG and EEG

Abstract: In recent years, it has been observed that there is an increasing rate of road accidents due to the low vigilance of drivers. Thus, the estimation of drivers' vigilance state plays a significant role in Public Transportation Safety (PTS). We have adopted a feature fusion strategy that combines the electroencephalogram (EEG) signals collected from various sites of the human brain, including forehead, temporal, and posterior and forehead electrooculogram (forehead-EOG) signals, to address this factor. The level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 65 publications
(88 reference statements)
1
14
0
Order By: Relevance
“…In this study, eight feature level fusion methods were selected for comparison, including SVR, CCNF and CCRF [2], DAE [3], GELM [15], LSTM [16], DNNSN [17], and LSTM-CapsAtt [14]. The DNNSN proposes a double-layer neural network with subnetwork nodes.…”
Section: Comparison Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, eight feature level fusion methods were selected for comparison, including SVR, CCNF and CCRF [2], DAE [3], GELM [15], LSTM [16], DNNSN [17], and LSTM-CapsAtt [14]. The DNNSN proposes a double-layer neural network with subnetwork nodes.…”
Section: Comparison Methodsmentioning
confidence: 99%
“…This method explores time-dependent information and significantly improves the performance of vigilance estimation. The authors of [17] proposed a double-layered neural network with subnetwork nodes (DNNSN), which is composed of several subnet nodes, and each node is composed of many hidden nodes with various feature selection capabilities. Zhang [14] suggested that the capsule attention model and deep LSTM should be integrated with EEG and EEG.…”
Section: Introductionmentioning
confidence: 99%
“…In [13], the use of an LSTM network resulted in a considerable improvement using feature fusion over single-mode EEG and EOG. In [12], a Doublelayered Neural Network with Subnetwork Nodes (DNNSN) was utilized along with multimodal feature selection using an autoencoder, obtaining impressive results. In [29], two domain adaption networks, notably Domain-Adversarial Neural Network (DANN) and Adversarial Discriminative Domain Adaptation (ADDA) were employed with feature fusion.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, EEG and EOG are susceptible to artifacts caused by motion and muscle activity such as jaw motion, frowning, and others, making their interpretation particularly challenging [14], [15]. Lastly, multimodal analysis of biological signals is generally difficult since identifying the complementary and contradicting information in the available signals is a challenging [12].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of deep learning techniques have been used to learn the most discriminative features extracted from EEG for affective computing. For example, In [7], the authors adopted Double-Layered Neural Network with Subnetwork Nodes (DNNSN) to estimate drivers' vigilance levels . In [8], a Graph regularized Extreme Learning Machine (GELM) was employed to predict fatigue .…”
Section: Related Workmentioning
confidence: 99%